Step-by-step testing and selection of generators components of pseudorandom sequences - Казакова, Н.Ф. (Eastern-European Journal of Enterprise Technologies, 2010)
Theoretical principles of the frequency testing of pseudorandom cryptography sequences and methods of their practical implementation are considered. The new method of step-by-step testing and selection of composite elemen generators of pseudorandom sequences is resulted.